KATA-KATA KASAR DALAM BAHASA JAWA - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This article deals with Javanese indecent words in relation to the state and activities to which such expressions can be applied. A careful study of the data elicited from two native informants shows that in addition to their ngoko and krama equivalents, indecent expressions are found in some things and activities in Javanese. The appropriate use of these indicent words should be understood in order to better understand the Javanese community, and to communicate better with them.